To solve the problem, we first need to define Andrea’s age in terms of Tony’s age.
Let:
- \( a \) = Tony’s current age
- \( a - 6 \) = Andrea’s current age (since Andrea is 6 years younger than Tony)
In two years:
- Tony’s age will be \( a + 2 \)
- Andrea’s age will be \( (a - 6) + 2 = a - 4 \)
According to the problem, in two years, Tony will be three times as old as Andrea:
\[ a + 2 = 3(a - 4) \]
Now, let's simplify this equation:
\[ a + 2 = 3a - 12 \]
Rearranging gives us:
\[ a - 3a = -12 - 2 \] \[ -2a = -14 \] \[ a = 7 \]
So, Tony's current age is 7 and Andrea's age is \( 7 - 6 = 1 \).
Now, let's check the response options given:
-
\( a + 2 = 3(a - 6 + 2) \)
- \( a + 2 = 3(a - 4) \) (this one is correct)
-
\( a + 2 = 3(a + 6 + 2) \)
- This does not represent the scenario correctly.
-
\( a = 3(a + 2) \)
- This does not represent the scenario correctly.
-
\( 3(a + 2) = a - 6 + 2 \)
- This simplifies to \( 3(a + 2) = a - 4 \) (not correct)
The correct equation that can be used to find Andrea’s and Tony’s current ages is:
\( a + 2 = 3(a - 4) \), which corresponds to the first option you provided:
\( a + 2 = 3(a - 6 + 2) \) or simply the rearranged version \( a + 2 = 3(a - 4) \).